Machiavellianism and its Relation to Aggressive Behavior (A field study in a sample of adolescents in Lattakia) - Kahileh, Reem; Martakoush, Sherine (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Research was conducted on a sample of adolescents in latakia. It consisted of (70) teenagers. The researcher used the Machiavellianism scale (Gies&Christie,1970) and aggressive behavior scale(prepared by the researcher). The study aimed to identify: - The relationship between Machiavellianism and aggressive behavior. - The differences between male and female in Machiavellianism - The differences between male and female in aggressive behavior Researcher found the following results: There is no statistically significant relationship between Machiavellianism and aggressive behavior. There are no statistically significant difference between male and female in Machiavellianism and aggressive behavior